Digital economy: theory, practice and perspective - I. D. Matskulyak; V. D. Kuligin; D. I. Matskulyak; N. N.Z.-O. Nagdaliev (Вестник университета)
The purpose of the publication is to clarify the content of the concept of the digital economy and to draw the attention of management personnel public authorities and business, as well as employers, legislators, scientists and others to this issue. Research methodology is based on a double phrase “digital economy”, consisting of both a digital phenomenon and, in fact, an economy, which required the separation and analysis of each term separately. We apply the well-known postulate about generality and peculiarities in the development of similar economic phenomena, which are the economy and its digital part in the article. The results obtained include generalization of the theoretical views of researchers on the digital economy as a social phenomenon and scientific concept, as well as its application in the practice of domestic management. Various approaches to understanding the digital economy, including the denial of this phenomenon have been compared. The thesis about the general laws of economic development in general and the digital economy in particular has been substantiated. Threats, dangers challenges of the phenomenon under consideration have been indicated. The conclusion on the need for accelerated development of a major scientific and technical project for the development of the digital economy in the country and its persistent implementation has been formulated.